Purification treatment process of copper anode slime

Through a process including pretreatment, metal gel capture agent preparation, vacuum inductance deselenium and precious metal capture, the problems of low recycling and purification rate of precious metals and uneven distribution of impurities in copper anode mud are solved, and efficient precious metal recycling and impurity removal are achieved.

CN119710259AActive Publication Date: 2025-03-28SHANGRAO HEFENG COPPER IND CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411699429.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-26
Publication Date
2025-03-28
Estimated Expiration
2044-11-26

AI Technical Summary

Technical Problem

In the existing copper anode sludge purification process, the recycling and purification rate of precious metals is low, and the impurities are unevenly distributed, which affects the separation effect.

Method used

A process is adopted, including pretreatment of copper anode mud, preparation of metal gel capture agents, vacuum inductance deselenium and precious metal capture steps. This process achieves effective capture of precious metals and removal of impurities through the leaching system of sulfuric acid-zinc chloride-ammonium sulfate and high-pressure chlorine and oxygen environment.

Benefits of technology

It significantly reduces the impurity content in precious metals, improves the recycling and purification rate of precious metals, and enhances the impurity removal effect.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119710259A_ABST
    Figure CN119710259A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of comprehensive treatment of copper anode slime, in particular to a purification treatment process of copper anode slime. Comprising the following steps: pretreating the copper anode slime; preparing a metal gel capturing agent; performing vacuum inductance selenium removal on the copper, arsenic and tellurium removed anode mud; and capturing the noble metal of the selenium-removed anode slime silicon. By preparing the metal gel capturing agent, mutual contact of silicon dioxide, sodium carbonate, bismuth oxide and carbon fibers with metal elements in the selenium-removed anode gold mud in a three-dimensional space can be increased, so that the contact area is increased, and the slagging reaction of silicon dioxide and sodium carbonate with impurity elements such as arsenic and antimony is strengthened; and moreover, the capability of reducing bismuth oxide by the carbon element is further enhanced, so that the elemental bismuth can better capture gold and silver elements, impurity metals can better gather in slag, and the obtained bismuth-silver-gold alloy particles are high in purity and good in metal purification effect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of comprehensive treatment of copper anode mud, and in particular to a purification treatment process of copper anode mud. Background Art

[0002] Copper anode mud is the impurity sediment precipitated from the anode copper plate during the copper smelting process. Its main components include oxides and sulfides of elements such as gold (Au), silver (Ag), arsenic (As), antimony (Sb), bismuth (Bi), tellurium (Te), selenium (Se) and copper. The purification process of copper anode mud aims to recover valuable metals (such as gold, silver, bismuth, selenium, etc.) from these impurity sediments, and remove harmful substances (such as arsenic, antimony, etc.) to achieve efficient resource recovery and environmental protection.

[0003] At present, the main methods for treating copper anode mud at home and abroad are pyrometallurgical process, hydrometallurgical process, semi-wet process, combined beneficiation and smelting process, and Kaldo furnace pyrometallurgical process. Generally speaking, it is divided into pyrometallurgical process and hydrometallurgical process. The hydrometallurgical process generally has problems such as complicated procedures, many auxiliary materials and three wastes, while the pyrometallurgical process mainly uses reducing agents such as coke, slag-forming agents such as silicon dioxide and sodium carbonate, and precious metal collectors to eutectic with copper anode mud to separate impurity metals and precious metals, and then recover the precious metals. However, in this process, the reducing agents, slag-forming agents and precious metal collectors are often unevenly distributed in the copper anode mud due to density quality problems and large gaps between powders. They cannot fully contact with metal ions in the early stage of eutectic, which reduces the uniformity of the eutectic, thereby worsening the effect of separating impurity metals and precious metals, thereby affecting the recovery and purification rate of precious metals. Summary of the invention

[0004] In order to solve the above technical defects, the present invention has developed a purification process for copper anode mud, which greatly reduces the content of impurities in precious metals and improves the recovery and purification rate of precious metals.

[0005] A purification process for copper anode mud comprises the following steps:

[0006] S1: Pretreatment of copper anode mud

[0007] The copper anode mud, sulfuric acid solution, zinc chloride and ammonium sulfate are uniformly mixed to obtain a copper anode mud slurry, the copper anode mud slurry is placed in a mixed gas atmosphere of chlorine and oxygen, stirred and ultrasonically treated, cooled and depressurized, and then filtered to obtain a filter residue and a filtrate, and the filter residue is dried to obtain a decoppered arsenic tellurium anode mud;

[0008] S2: Preparation of metal gel capture agent

[0009] Putting tetraethyl orthosilicate, anhydrous ethanol and deionized water in a container, adding sodium carbonate and bismuth oxide and stirring after adjusting the pH, and letting it stand to obtain a composite gel, and evenly dispersing the composite gel into carbon fiber felt by vacuum impregnation, and then soaking it in anhydrous ethanol after drying, and then drying to obtain a metal gel capture agent;

[0010] S3: Vacuum induction deselenization of copper-arsenic-tellurium anode mud

[0011] The copper-removed arsenic-tellurium anode mud, concentrated sulfuric acid and hydrogen peroxide are mixed and stirred uniformly, and then heated to obtain mature anode mud. The mature anode mud is subjected to electromagnetic induction heating in a vacuum, and the generated gas is absorbed by a sodium sulfite solution. The solid matter is cooled to obtain the deselenized anode mud.

[0012] S4: Precious metal capture of silicon from deselenized anode mud

[0013] The deselenized anode mud and the metal gel capture agent are mixed evenly and then heated at high temperature to obtain a mixed metal material. The mixed metal material is crushed to obtain slag and bismuth-silver-gold alloy particles. The bismuth-silver-gold alloy particles are distilled and chlorinated to obtain gold separation liquid and silver powder. The gold separation liquid is reduced with oxalic acid to obtain gold powder.

[0014] Furthermore, step S1 of pre-treating the copper anode mud comprises the following steps:

[0015] S1.1: 8-10 parts by weight of copper anode mud is placed in the inner tank of a reactor, and then a sulfuric acid solution with a concentration of 3.5-4 mol / L is added at a solid-liquid ratio of 1:(10-12), and then zinc chloride and ammonium sulfate are added in sequence, and the concentration of zinc chloride in the inner tank is controlled to be 2.5-3 mol / L, and the concentration of ammonium sulfate is controlled to be 1.5-2 mol / L, and the copper anode mud slurry is obtained after being stirred evenly with a glass rod;

[0016] S1.2: Transfer the inner tank of the reactor filled with copper anode mud to a reactor equipped with an ultrasonic generator, an air valve and a stirring device, seal the reactor, set the temperature to 60-65℃, the stirring speed to 200-250rpm, and the ultrasonic frequency to 15-20KHz. After heating to the set temperature, introduce a mixed gas of chlorine and oxygen into the reactor through the air valve to make the pressure in the reactor reach 0.6-0.8MPa. At this time, stop ventilation, stir for 2-2.5 hours, and then ultrasonicate for 30-40 minutes. Then, cool down to 30-35℃ naturally with the reactor and release the pressure to normal pressure. Filter to obtain filter residue and filtrate, and place the filter residue in a drying oven to dry at 60-70℃ to obtain decoppered tellurium arsenic anode mud.

[0017] Furthermore, the preparation of the metal gel capture agent in step S2 comprises the following steps:

[0018] S2.1: Put tetraethyl orthosilicate, anhydrous ethanol and deionized water in a container in a mass ratio of 1:(3-4):(4-5), slowly drop hydrochloric acid solution into it under stirring, adjust the pH value to 2-3, heat it to 75-85°C and keep stirring for 2-3 hours, then drop ammonia water to adjust the pH value to 6-7, then add sodium carbonate and bismuth oxide, continue stirring for 15-20 minutes, and then let it stand to obtain a composite gel;

[0019] S2.2: Take 1-2 parts by weight of carbon fiber felt with a pore size of 1-2 mm and place it in a mold, pour in 3-4 parts by weight of composite gel, and then put it into a vacuum impregnation machine to evenly disperse the composite gel into the carbon fiber felt by vacuum impregnation. After drying in an oven at 40-45°C for 3-4 hours, soak it in anhydrous ethanol for 20-24 hours, and then place it in an oven at 120-150°C and dry it for 1.5-2 hours to obtain a metal gel capture agent.

[0020] Furthermore, step S3 of vacuum induction deselenization of copper-arsenic-tellurium anode mud comprises the following steps:

[0021] S3.1: the copper-removed arsenic-tellurium anode mud obtained in step S1.2, 6-8 parts by weight of concentrated sulfuric acid with a concentration of 98% and 2-3 parts by weight of hydrogen peroxide are mixed and stirred evenly, and then placed in an oven and heated at a temperature of 100-120° C. for 1-1.5 hours to obtain mature anode mud;

[0022] S3.2: Place the mature anode mud in an electromagnetic induction heating tubular furnace, pump the pressure in the furnace to 40-60kPa, introduce air and control the air flow rate to 200-220L / h, then heat it to 380-400℃ at a heating rate of 10-15℃ / min, and keep it warm for 15-20 minutes of roasting. The gas discharged from the electromagnetic induction heating tubular furnace is absorbed by 2-3 times of sodium sulfite solution. The solid matter in the electromagnetic induction heating tubular furnace is taken out and cooled to room temperature to obtain deselenized anode mud.

[0023] Furthermore, step S4, the capture of precious metals from the deselenized anode mud silicon, comprises the following steps:

[0024] S4.1: Place the deselenized anode mud and the metal gel capture agent in a mass ratio of 1: (1-1.5) in a high-speed stirrer at a stirring speed of 800-1000 rpm and stir them uniformly, then place them in a tubular furnace, introduce nitrogen for 3-5 minutes, seal the tubular furnace, heat to 900-950°C at a heating rate of 8-10°C / min, keep the temperature for 6-8 hours, and then cool to 30-45°C to obtain a mixed metal material;

[0025] S4.2: The mixed metal material is placed in a crusher and crushed for 10-15 minutes, and the crushed particle size is controlled at 2-3mm. Then, the metal particles and the slag are selected and separated to obtain bismuth-silver-gold alloy particles. The bismuth-silver-gold alloy particles are placed under a pressure of 3-4Pa and distilled at a temperature of 1000-1050°C for 2-2.5 hours to obtain gold-rich silver slag. The gold-rich silver slag is subjected to gold separation by chlorination to obtain gold separation liquid and silver powder. The gold separation liquid is reduced by oxalic acid to obtain gold powder.

[0026] Furthermore, in the mixed gas of chlorine and oxygen introduced into the reactor in step S1.2, the volume ratio of chlorine to oxygen is 1:(4-5).

[0027] Furthermore, in step S2.1, the mass fraction of sodium carbonate accounts for 10-20wt% of the total mass of ethyl orthosilicate, anhydrous ethanol and deionized water, and the mass fraction of bismuth oxide accounts for 30-50wt%.

[0028] The beneficial effects are as follows: 1. In the process of preparing silica gel from ethyl orthosilicate, sodium carbonate and bismuth oxide are added to obtain a composite gel, and then the composite gel is dispersed into the carbon fiber felt, so that the composite gel can fully and evenly coat and penetrate the carbon fiber. The prepared metal gel capture agent has certain strength and molding ability, and the silica, sodium carbonate, bismuth oxide and carbon fiber components are evenly distributed. In the subsequent high-speed stirring process with the deselenium anode gold mud, each component can be fully contacted with the metal elements in the deselenium anode gold mud in a three-dimensional space, increasing the contact area, and can also maintain a solidified state in the early stage of slag formation to avoid uneven dispersion of each component due to quality reasons, strengthen the slag formation reaction of silica and sodium carbonate with impurity elements such as arsenic and antimony, and further enhance the ability of carbon to reduce bismuth oxide, so that the bismuth element can better capture the gold and silver elements, and can make the impurity metals better aggregate in the slag, and the obtained bismuth-silver-gold alloy particles Au and Ag have high purity and good metal purification effect.

[0029] 2. The present invention constructs a sulfuric acid-zinc chloride-ammonium sulfate leaching system to leach copper anode mud. In a high-pressure environment where chlorine and oxygen are introduced, the Ag element is easily leached with Cl - Combined with sulfate to form AgCl precipitation, Pb combines with sulfate to form PbSO4 precipitation, Au element is stable and does not react, Se element forms Ag2Se precipitation with Ag, all of which are enriched in the filter residue, and Cu element is converted into CuSO4 in an acidic system, As, Sb, Bi and Te are also leached in the chloride salt system and the high-pressure environment of chlorine and oxygen, and the zinc ions introduced in the present application can form soluble complexes with As and Sb, first promoting the leaching of As and Sb, and then dissolving them in the filtrate, reducing the component of impurities in the decoppered tellurium arsenic anode mud, thereby avoiding interference with the subsequent recovery of precious metals.

[0030] 3. The present invention performs vacuum electromagnetic induction selenium evaporation by mixing and maturing decoppered arsenic tellurium anode mud, concentrated sulfuric acid and hydrogen peroxide. Selenium oxide can volatilize at a lower boiling temperature in a vacuum, and hydrogen peroxide is added as an oxidant to prevent insufficient selenium oxidation in a vacuum environment, which affects the purification effect and greatly improves the recovery rate of selenium. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 This is a process flow chart of the purification of copper anode mud used in an embodiment of the present invention. DETAILED DESCRIPTION

[0032] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0033] The main chemical components (wt%) of copper anode mud in the following embodiments of the present invention are: Cu17.8, Se8.34, Te2.17, Sb1.69, Bi0.13, As1.54, Pb2.45, Ni3.07, Au0.14, Ag20.25.

[0034] Example 1

[0035] A purification process for copper anode mud, such as Figure 1 As shown, the following steps are included:

[0036] S1: Pretreatment of copper anode mud

[0037] S1.1: 8 parts by weight of copper anode mud is placed in the inner tank of a reactor, and then a sulfuric acid solution with a concentration of 3.5 mol / L is added at a solid-liquid ratio of 1:10, and then zinc chloride and ammonium sulfate are added in sequence, and the concentration of zinc chloride in the inner tank is controlled to be 2.5 mol / L, and the concentration of ammonium sulfate is controlled to be 1.5 mol / L, and the copper anode mud slurry is obtained after being stirred evenly with a glass rod;

[0038] S1.2: Transfer the inner tank of the reactor filled with copper anode mud slurry to a reactor equipped with an ultrasonic generator, an air valve and a stirring device, seal the reactor, set the temperature to 60°C, the stirring speed to 200rpm, and the ultrasonic frequency to 15KHz. After heating to the set temperature, introduce a mixed gas of chlorine and oxygen in a volume ratio of 1:4 into the reactor through the air valve to make the pressure in the reactor reach 0.6MPa. At this time, stop ventilation, stir for 2 hours and then ultrasonicate for 30 minutes, then naturally cool down to 30°C with the reactor and release the pressure to normal pressure, filter to obtain filter residue and filtrate, place the filter residue in a drying oven and dry it at 60°C to obtain decoppered tellurium arsenic anode mud.

[0039] S2: Preparation of metal gel capture agent

[0040] S2.1: Put tetraethyl orthosilicate, anhydrous ethanol and deionized water in a container in a mass ratio of 1:3:4, slowly drip hydrochloric acid solution into it under stirring, adjust the pH to 2, heat to 75°C and keep stirring for 2 hours, then drip ammonia water to adjust the pH to 6, then add 10wt% sodium carbonate and 30wt% bismuth oxide, continue stirring for 15 minutes, and then let it stand to obtain a composite gel;

[0041] S2.2: Take 2 parts by weight of carbon fiber felt with a pore size of 1 mm and place it in a mold, pour in 4 parts by weight of composite gel, and then put it into a vacuum impregnation machine to evenly disperse the composite gel into the carbon fiber felt by vacuum impregnation. After drying in an oven at 40°C for 3 hours, soak it in anhydrous ethanol for 20 hours, and then place it in an oven at 120°C and dry it for 1.5 hours to obtain a metal gel capture agent.

[0042] S3: Vacuum induction deselenization of copper-arsenic-tellurium anode mud

[0043] S3.1: the copper-free arsenic-tellurium anode mud obtained in step S1.2, 6 parts by weight of concentrated sulfuric acid with a concentration of 98% and 2 parts by weight of hydrogen peroxide are mixed and stirred evenly, and then placed in an oven and heated at a temperature of 100° C. for 1 hour to obtain mature anode mud;

[0044] S3.2: Place the mature anode mud in an electromagnetic induction heating tubular furnace, pump the pressure in the furnace to 40 kPa, introduce air and control the air flow rate to 200 L / h, then heat up to 380°C at a heating rate of 10°C / min, and keep warm for 15 minutes for roasting. The gas discharged from the electromagnetic induction heating tubular furnace is absorbed by sodium sulfite solution twice. The solid matter in the electromagnetic induction heating tubular furnace is taken out and cooled to room temperature to obtain deselenized anode mud.

[0045] S4: Precious metal capture of silicon from deselenized anode mud

[0046] S4.1: Place the deselenized anode mud and the metal gel capture agent in a mass ratio of 1:1 in a high-speed stirrer at a stirring speed of 800 rpm and stir them uniformly, then place them in a tube furnace, introduce nitrogen for 3 minutes and seal the tube furnace, heat to 900°C at a heating rate of 8°C / min, keep the temperature for 6 hours, and then cool to 30°C to obtain a mixed metal material;

[0047] S4.2: The mixed metal material is placed in a crusher and crushed for 10 minutes with the crushed particle size controlled at 2 mm. The metal particles and slag are then selected and separated to obtain bismuth-silver-gold alloy particles. The bismuth-silver-gold alloy particles are placed under a pressure of 3 Pa and distilled at a temperature of 1000°C for 2 hours to obtain gold-rich silver slag. The gold-rich silver slag is subjected to gold separation by chlorination to obtain gold separation liquid and silver powder. The gold separation liquid is reduced with oxalic acid to obtain gold powder.

[0048] Example 2

[0049] A purification process for copper anode mud, such as Figure 1 As shown, the following steps are included:

[0050] S1: Pretreatment of copper anode mud

[0051] S1.1: 10 parts by weight of copper anode mud is placed in the inner tank of a reactor, and then a sulfuric acid solution with a concentration of 4 mol / L is added at a solid-liquid ratio of 1:12, and then zinc chloride and ammonium sulfate are added in sequence, the concentration of zinc chloride in the inner tank is controlled to be 3 mol / L, and the concentration of ammonium sulfate is controlled to be 2 mol / L, and the copper anode mud slurry is obtained after being stirred evenly with a glass rod;

[0052] S1.2: Transfer the inner tank of the reactor filled with copper anode mud slurry to a reactor equipped with an ultrasonic generator, an air valve and a stirring device, seal the reactor, set the temperature to 60°C, the stirring speed to 200rpm, and the ultrasonic frequency to 15KHz. After heating to the set temperature, introduce a mixed gas of chlorine and oxygen in a volume ratio of 1:5 into the reactor through the air valve to make the pressure in the reactor reach 0.6MPa. At this time, stop ventilation, stir for 2 hours and then ultrasonicate for 30 minutes, then naturally cool down to 30°C with the reactor and release the pressure to normal pressure, filter to obtain filter residue and filtrate, place the filter residue in a drying oven and dry it at 60°C to obtain decoppered tellurium arsenic anode mud.

[0053] S2: Preparation of metal gel capture agent

[0054] S2.1: Put tetraethyl orthosilicate, anhydrous ethanol and deionized water in a container in a mass ratio of 1:4:5, slowly drop hydrochloric acid solution into it under stirring, adjust the pH to 2, heat to 75°C and keep stirring for 2 hours, then drop ammonia water to adjust the pH to 6, then add 20wt% sodium carbonate and 50wt% bismuth oxide, continue stirring for 15 minutes, and then let it stand to obtain a composite gel;

[0055] S2.2: Take 1 weight part of carbon fiber felt with a pore size of 2 mm and place it in a mold, pour in 3 weight parts of composite gel, and then put it into a vacuum impregnation machine to evenly disperse the composite gel into the carbon fiber felt by vacuum impregnation. After drying in an oven at 40°C for 3 hours, soak it in anhydrous ethanol for 20 hours, and then place it in an oven at 120°C and dry it for 1.5 hours to obtain a metal gel capture agent.

[0056] S3: Vacuum induction deselenization of copper-arsenic-tellurium anode mud

[0057] S3.1: the copper-removed arsenic-tellurium anode mud obtained in step S1.2, 8 parts by weight of concentrated sulfuric acid with a concentration of 98% and 3 parts by weight of hydrogen peroxide are mixed and stirred evenly, and then placed in an oven and heated at a temperature of 100° C. for 1 hour to obtain matured anode mud;

[0058] S3.2: Place the mature anode mud in an electromagnetic induction heating tubular furnace, pump the pressure in the furnace to 40 kPa, introduce air and control the air flow rate to 200 L / h, then heat up to 380°C at a heating rate of 10°C / min, and keep warm for 15 minutes for roasting. The gas discharged from the electromagnetic induction heating tubular furnace is absorbed by sodium sulfite solution twice. The solid matter in the electromagnetic induction heating tubular furnace is taken out and cooled to room temperature to obtain deselenized anode mud.

[0059] S4: Precious metal capture of silicon from deselenized anode mud

[0060] S4.1: Place the deselenized anode mud and the metal gel capture agent in a mass ratio of 1:1.5 in a high-speed stirrer at a stirring speed of 800 rpm and stir them uniformly. Then place them in a tubular furnace, introduce nitrogen for 3 minutes, seal the tubular furnace, heat to 900°C at a heating rate of 8°C / min, keep the temperature for 6 hours, and then cool to 30°C to obtain a mixed metal material.

[0061] S4.2: The mixed metal material is placed in a crusher and crushed for 10 minutes with the crushed particle size controlled at 2 mm. The metal particles and slag are then selected and separated to obtain bismuth-silver-gold alloy particles. The bismuth-silver-gold alloy particles are placed under a pressure of 3 Pa and distilled at a temperature of 1000°C for 2 hours to obtain gold-rich silver slag. The gold-rich silver slag is subjected to gold separation by chlorination to obtain gold separation liquid and silver powder. The gold separation liquid is reduced with oxalic acid to obtain gold powder.

[0062] Example 3

[0063] A purification process for copper anode mud, such as Figure 1 As shown, the following steps are included:

[0064] S1: Pretreatment of copper anode mud

[0065] S1.1: 8 parts by weight of copper anode mud is placed in the inner tank of a reactor, and then a sulfuric acid solution with a concentration of 3.5 mol / L is added at a solid-liquid ratio of 1:10, and then zinc chloride and ammonium sulfate are added in sequence, and the concentration of zinc chloride in the inner tank is controlled to be 2.5 mol / L, and the concentration of ammonium sulfate is controlled to be 1.5 mol / L, and the copper anode mud slurry is obtained after being stirred evenly with a glass rod;

[0066] S1.2: Transfer the inner tank of the reactor filled with copper anode mud slurry to a reactor equipped with an ultrasonic generator, an air valve and a stirring device, seal the reactor, set the temperature to 65°C, the stirring speed to 250rpm, and the ultrasonic frequency to 20KHz. After heating to the set temperature, introduce a mixed gas of chlorine and oxygen in a volume ratio of 1:4 into the reactor through the air valve to make the pressure in the reactor reach 0.8MPa. At this time, stop ventilation, stir for 2.5 hours and then ultrasonicate for 40 minutes, then naturally cool down to 35°C with the reactor and release the pressure to normal pressure, filter to obtain filter residue and filtrate, place the filter residue in a drying oven and dry it at 70°C to obtain decoppered tellurium arsenic anode mud.

[0067] S2: Preparation of metal gel capture agent

[0068] S2.1: Put tetraethyl orthosilicate, anhydrous ethanol and deionized water in a container in a mass ratio of 1:3:4, slowly drop hydrochloric acid solution into it under stirring, adjust the pH to 3, heat to 85°C and keep stirring for 3 hours, then drop ammonia water to adjust the pH to 7, then add 10wt% sodium carbonate and 30wt% bismuth oxide, continue stirring for 20 minutes, and then let it stand to obtain a composite gel;

[0069] S2.2: Take 2 parts by weight of carbon fiber felt with a pore size of 1 mm and place it in a mold, pour in 4 parts by weight of the composite gel, and then put it into a vacuum impregnation machine to evenly disperse the composite gel into the carbon fiber felt by vacuum impregnation. After drying in an oven at 45°C for 4 hours, soak it in anhydrous ethanol for 24 hours, and then place it in an oven at 150°C and dry it for 2 hours to obtain a metal gel capture agent.

[0070] S3: Vacuum induction deselenization of copper-arsenic-tellurium anode mud

[0071] S3.1: the copper-free arsenic-tellurium anode mud obtained in step S1.2, 6 parts by weight of concentrated sulfuric acid with a concentration of 98% and 2 parts by weight of hydrogen peroxide are mixed and stirred evenly, and then placed in an oven and heated at a temperature of 120° C. for 1.5 hours to obtain mature anode mud;

[0072] S3.2: Place the mature anode mud in an electromagnetic induction heating tubular furnace, pump the pressure in the furnace to 60 kPa, introduce air and control the air flow rate to 220 L / h, then heat up to 400°C at a heating rate of 15°C / min, and keep warm for 20 minutes for roasting. The gas discharged from the electromagnetic induction heating tubular furnace is absorbed by sodium sulfite solution three times. The solid matter in the electromagnetic induction heating tubular furnace is taken out and cooled to room temperature to obtain deselenized anode mud.

[0073] S4: Precious metal capture of silicon from deselenized anode mud

[0074] S4.1: The deselenized anode mud and the metal gel capture agent are placed in a high-speed stirrer at a mass ratio of 1:1 and stirred at a high speed of 1000 rpm, and then placed in a tube furnace, nitrogen is introduced for 5 minutes, and then the tube furnace is sealed, and heated to 950°C at a heating rate of 10°C / min, and then kept warm for 8 hours, and then cooled to 45°C to obtain a mixed metal material;

[0075] S4.2: The mixed metal material is placed in a crusher and crushed for 15 minutes. The crushed particle size is controlled at 3 mm. Then, the metal particles and slag are selected and separated to obtain bismuth-silver-gold alloy particles. The bismuth-silver-gold alloy particles are placed under a pressure of 4 Pa ​​and distilled at a temperature of 1050°C for 2.5 hours to obtain gold-rich silver slag. The gold-rich silver slag is subjected to gold separation by chlorination to obtain gold separation liquid and silver powder. The gold separation liquid is reduced with oxalic acid to obtain gold powder.

[0076] Comparative Example 1

[0077] Compared with Example 1, the difference of Comparative Example 1 is that Comparative Example 1 removes step S2 and directly replaces the metal gel capture agent with a mixed powder of coke, sodium carbonate, silicon dioxide and bismuth oxide in an equal mass ratio of 1:10:10:30 in step S4.1, and the remaining steps are the same as Example 1.

[0078] Comparative Example 2

[0079] Compared with Example 1, the difference of Comparative Example 2 is that, in Comparative Example 2, zinc chloride and ammonium sulfate in step S1.1 are replaced with sodium chloride and sodium sulfate of equal mass, and the remaining steps are the same as those in Example 1, and the remaining steps are the same as those in Example 1 to obtain copper-removed tellurium-arsenic anode mud.

[0080] Comparative Example 3

[0081] Compared with Example 1, the difference of Comparative Example 3 is that, in Comparative Example 3, step S1.2 is removed, and the copper anode mud slurry prepared in step S1.1 is directly heated at 60° C. in an oxygen atmosphere, and the remaining steps are the same as those in Example 1 to obtain decoppered tellurium arsenic anode mud.

[0082] Comparative Example 4

[0083] Compared with Example 1, the difference of Comparative Example 4 is that, in Comparative Example 4, step S3 is removed, and the decoppered tellurium arsenic anode mud obtained in step S1.2 is directly roasted at 380° C. under the condition of an oxygen flow rate of 200 L / h, and the remaining steps are the same as in Example 1 to obtain deselenized anode mud.

[0084] Experiment 1: Take 6 portions of 1000g copper anode mud, each three portions as a group are divided into two groups, one group corresponds to Example 1, and the other group corresponds to Comparative Example 1. Each portion in each group is prepared into bismuth-silver-gold alloy particles by the processes of Example 1 and Comparative Example 1, and the purity of Au and Ag after removing the bismuth element is measured by ICP-MS characterization to avoid inaccurate data caused by bismuth in the metal gel capture agent added subsequently. The data is recorded and tabulated, as shown in Table 1. It can be seen that the purity of Example 1 is higher than the gold purity of Comparative Example 1, which can prove that adding a metal gel capture agent to the deselenized anode gold mud for slag-forming reaction can strengthen the slag-forming reaction of silicon dioxide and sodium carbonate with impurity elements such as arsenic and antimony, and enable the bismuth element to better capture gold and silver elements, thereby increasing the metal purification effect.

[0085] Table 1: Purity of Au and Ag

[0086] purity / % Au Ag Example 1 0.68 99.26 Comparative Example 1 0.67 98.25

[0087] Experiment 2: 9 portions of 1000g copper anode mud were taken, and each group of three portions was divided into three groups, one group corresponding to Example 1, one group corresponding to Comparative Example 2, and one group corresponding to Comparative Example 3. Each portion of each group was used to prepare a filtrate by the processes of Example 1, Comparative Example 2 and Comparative Example 3, and the contents of Cu, Sb and As impurity metals in the filtrate were measured by ICP-MS characterization. The average value of each group was calculated, and then the impurity metal leaching rate was calculated, and the impurity metal leaching rate = the average value of the impurity metal content in the filtrate / the average value of the impurity metal content in the copper anode mud × 100%, and a table was prepared as shown in Table 2. It can be seen that the impurity metal leaching rate of Example 1 is higher than the impurity metal leaching rate of Comparative Examples 2-3, which can prove that the construction of a sulfuric acid-zinc chloride-ammonium sulfate leaching system and heating in a chlorine and oxygen high-pressure gas environment can improve the leaching rates of Cu, Sb and As.

[0088] Table 2: Impurity metal leaching rate

[0089] Impurity metal leaching rate / % Cu Sb As Example 1 99.83 98.98 96.23 Comparative Example 2 97.12 97.34 95.54 Comparative Example 3 96.23 97.02 95.15

[0090] Experiment 3: Take 6 portions of 1000g copper anode mud, and divide three portions into two groups, one group corresponding to Example 1, and the other group corresponding to Comparative Example 4. Each portion in each group is used to prepare deselenized anode mud by the processes of Example 1 and Comparative Example 4, and the selenium metal content therein is measured by ICP-MS characterization. The average value of each group is calculated, and then compared with the average content of the above components in the copper anode mud, and the direct recovery of selenium is calculated. The direct recovery of selenium = 1-selenium metal content in deselenized anode mud / selenium metal content in copper anode mud × 100%, and a table is prepared as shown in Table 3. It can be seen that the direct recovery of selenium in Example 1 is higher than that in Comparative Example 4, which can prove that vacuum inductive deselenization can greatly improve the recovery rate of selenium.

[0091] Table 3: Direct yield of selenium

[0092] Copper anode mud Example 1 Comparative Example 4 Selenium content / g 83.4 80.6 75.7 Direct yield of selenium / % 96.6 90.8

[0093] The above embodiments are merely illustrative of the principles and effects of the present invention, and are not intended to limit the present invention. Anyone familiar with the art may modify or alter the above embodiments without departing from the spirit and scope of the present invention. Therefore, all equivalent modifications or alterations made by a person of ordinary skill in the art without departing from the spirit and technical concept disclosed by the present invention shall still be covered by the claims of the present invention.

Claims

1. A purification process for copper anode mud, characterized in that: The following steps are involved: S1: Pretreatment of copper anode mud The copper anode mud, sulfuric acid solution, zinc chloride and ammonium sulfate are uniformly mixed to obtain a copper anode mud slurry, the copper anode mud slurry is placed in a mixed gas atmosphere of chlorine and oxygen, stirred and ultrasonically treated, cooled and depressurized, and then filtered to obtain a filter residue and a filtrate, and the filter residue is dried to obtain a decoppered arsenic tellurium anode mud; S2: Preparation of metal gel capture agent Putting tetraethyl orthosilicate, anhydrous ethanol and deionized water in a container, adding sodium carbonate and bismuth oxide and stirring after adjusting the pH, and letting it stand to obtain a composite gel, and evenly dispersing the composite gel into carbon fiber felt by vacuum impregnation, and then soaking it in anhydrous ethanol after drying, and then drying to obtain a metal gel capture agent; S3: Vacuum induction deselenization of copper-arsenic-tellurium anode mud The copper-removed arsenic-tellurium anode mud, concentrated sulfuric acid and hydrogen peroxide are mixed and stirred uniformly, and then heated to obtain mature anode mud. The mature anode mud is subjected to electromagnetic induction heating in a vacuum, and the generated gas is absorbed by a sodium sulfite solution. The solid matter is cooled to obtain the deselenized anode mud. S4: Precious metal capture of silicon from deselenized anode mud The deselenized anode mud and the metal gel capture agent are mixed evenly and then heated at high temperature to obtain a mixed metal material. The mixed metal material is crushed to obtain slag and bismuth-silver-gold alloy particles. The bismuth-silver-gold alloy particles are distilled and chlorinated to obtain gold separation liquid and silver powder. The gold separation liquid is reduced with oxalic acid to obtain gold powder.

2. The process for purifying copper anode mud according to claim 1, characterized in that: Step S1: pretreatment of copper anode mud, comprising the following steps: S1.1: 8-10 parts by weight of copper anode mud is placed in the inner tank of a reactor, and then a sulfuric acid solution with a concentration of 3.5-4 mol / L is added at a solid-liquid ratio of 1:(10-12), and then zinc chloride and ammonium sulfate are added in sequence, and the concentration of zinc chloride in the inner tank is controlled to be 2.5-3 mol / L, and the concentration of ammonium sulfate is controlled to be 1.5-2 mol / L, and the copper anode mud slurry is obtained after being stirred evenly with a glass rod; S1.2: Transfer the inner tank of the reactor filled with copper anode mud to a reactor equipped with an ultrasonic generator, an air valve and a stirring device, seal the reactor, set the temperature to 60-65℃, the stirring speed to 200-250rpm, and the ultrasonic frequency to 15-20KHz. After heating to the set temperature, introduce a mixed gas of chlorine and oxygen into the reactor through the air valve to make the pressure in the reactor reach 0.6-0.8MPa. At this time, stop ventilation, stir for 2-2.5 hours, and then ultrasonicate for 30-40 minutes. Then, cool down to 30-35℃ naturally with the reactor and release the pressure to normal pressure. Filter to obtain filter residue and filtrate, and place the filter residue in a drying oven to dry at 60-70℃ to obtain decoppered tellurium arsenic anode mud.

3. The process for purifying copper anode mud according to claim 1, characterized in that: Step S2: Preparation of metal gel capture agent, comprising the following steps: S2.1: Put tetraethyl orthosilicate, anhydrous ethanol and deionized water in a container in a mass ratio of 1:(3-4):(4-5), slowly drop hydrochloric acid solution into it under stirring, adjust the pH value to 2-3, heat it to 75-85°C and keep stirring for 2-3 hours, then drop ammonia water to adjust the pH value to 6-7, then add sodium carbonate and bismuth oxide, continue stirring for 15-20 minutes, and then let it stand to obtain a composite gel; S2.2: Take 1-2 parts by weight of carbon fiber with a pore size of 1-2mm and place it in a mold, pour in 3-4 parts by weight of composite gel, and then put it into a vacuum impregnation machine to evenly disperse the composite gel into the carbon fiber felt by vacuum impregnation. After drying in an oven at 40-45°C for 3-4 hours, soak it in anhydrous ethanol for 20-24 hours, and then place it in an oven at 120-150°C and dry it for 1.5-2 hours to obtain a metal gel capture agent.

4. The process for purifying copper anode mud according to claim 1, characterized in that: Step S3: vacuum induction deselenization of copper-arsenic-tellurium anode mud, comprising the following steps: S3.1: the copper-removed arsenic-tellurium anode mud obtained in step S1.2, 6-8 parts by weight of concentrated sulfuric acid with a concentration of 98% and 2-3 parts by weight of hydrogen peroxide are mixed and stirred evenly, and then placed in an oven and heated at a temperature of 100-120° C. for 1-1.5 hours to obtain mature anode mud; S3.2: Place the mature anode mud in an electromagnetic induction heating tubular furnace, pump the pressure in the furnace to 40-60kPa, introduce air and control the air flow rate to 200-220L / h, then heat it to 380-400℃ at a heating rate of 10-15℃ / min, and keep it warm for 15-20 minutes of roasting. The gas discharged from the electromagnetic induction heating tubular furnace is absorbed by 2-3 times of sodium sulfite solution. The solid matter in the electromagnetic induction heating tubular furnace is taken out and cooled to room temperature to obtain deselenized anode mud.

5. The process for purifying copper anode mud according to claim 2, characterized in that: Step S4 is to capture the precious metals of the deselenized anode mud silicon, comprising the following steps: S4.1: Place the deselenized anode mud and the metal gel capture agent in a mass ratio of 1: (1-1.5) in a high-speed stirrer at a stirring speed of 800-1000 rpm and stir them uniformly, then place them in a tubular furnace, introduce nitrogen for 3-5 minutes, seal the tubular furnace, heat to 900-950°C at a heating rate of 8-10°C / min, keep the temperature for 6-8 hours, and then cool to 30-45°C to obtain a mixed metal material; S4.2: The mixed metal material is placed in a crusher and crushed for 10-15 minutes, and the crushed particle size is controlled at 2-3mm. Then, the metal particles and the slag are selected and separated to obtain bismuth-silver-gold alloy particles. The bismuth-silver-gold alloy particles are placed under a pressure of 3-4Pa and distilled at a temperature of 1000-1050°C for 2-2.5 hours to obtain gold-rich silver slag. The gold-rich silver slag is subjected to gold separation by chlorination to obtain gold separation liquid and silver powder. The gold separation liquid is reduced by oxalic acid to obtain gold powder.

6. The process for purifying copper anode mud according to claim 2, characterized in that: In step S1.2, the volume ratio of chlorine to oxygen in the mixed gas of chlorine and oxygen introduced into the reactor is 1: (4-5)。 7. The process for purifying copper anode mud according to claim 3, characterized in that: The mass fraction of sodium carbonate in step S2.1 accounts for 10-20wt% of the total mass of ethyl orthosilicate, anhydrous ethanol and deionized water, and the mass fraction of bismuth oxide accounts for 30-50wt%.

Citation Information

Patent Citations

  • Technology for extracting selenium and copper from anode mud

    CN108342580A

  • Novel copper anode mud treatment process

    CN112609078A

  • Recovery method for valuable metals in copper anode slime

    CN113846222A

  • Method for capturing precious metal in copper anode slime by smelting green metal bismuth at low temperature

    CN118406881A

  • Method for processing anode slime of copperelectrolysis

    KR1020020096361A